2012
DOI: 10.1111/tra.12003
|View full text |Cite
|
Sign up to set email alerts
|

Rab7 and Arl8 GTPases are Necessary for Lysosome Tubulation in Macrophages

Abstract: Lysosomes provide a niche for molecular digestion and are a convergence point for endocytic trafficking, phagosome maturation and autophagy. Typically, lysosomes are small, globular organelles that appear punctate under the fluorescence microscope. However, activating agents like phorbol esters transform macrophage lysosomes into tubular lysosomes (TLs), which have been implicated in retention of pinocytic uptake and phagosome maturation. Moreover, dendritic cells exposed to lipopolysaccharides (LPSs) convert … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
146
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 132 publications
(153 citation statements)
references
References 43 publications
6
146
0
1
Order By: Relevance
“…Arl8b-regulated motility appears to be dependent upon its interaction with SifA and kinesin-interacting protein that binds the kinesin motor Kif5b. Moreover, Arl8b and these partners have been implicated in the control of lysosome tubulation in macrophages (24). Arl8b-depleted macrophages were unable to generate lysosomal tubules in response to LPS stimulation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Arl8b-regulated motility appears to be dependent upon its interaction with SifA and kinesin-interacting protein that binds the kinesin motor Kif5b. Moreover, Arl8b and these partners have been implicated in the control of lysosome tubulation in macrophages (24). Arl8b-depleted macrophages were unable to generate lysosomal tubules in response to LPS stimulation.…”
Section: Discussionmentioning
confidence: 99%
“…For example, Arl8b was shown to control the outward movement of lysosomes and lysosome-related organelles such as lytic granules in NK cells by recruiting SifA and kinesininteracting protein that, in turn, binds to the kinesin motor Kif5b (22,23). Recent studies also suggested that Arl8b plays a role in lysosomal tubulation in macrophages and in Salmonellainfected cells, a process that requires the recruitment of kinesin motors (24,25). Separately, we found that Arl8b directs certain cargo into lysosomes in mammals by recruiting the VPS41 subunit of the tethering HOPS complex that mediates the fusion of late endosomes to lysosomes, whereas others defined a similar role for Arl8b in Caenorhabditis elegans (21,26,27).…”
mentioning
confidence: 99%
“…Other perturbations, such as aggresome formation (Zaarur et al, 2014), starvation (Korolchuk et al, 2011), drug-induced apoptosis (Yu et al, 2016), expression of pathogenic mutant forms of huntingtin (Erie et al, 2015) or leucine-rich repeat kinase 2 (LRRK2) (Dodson et al, 2012) and LSDs (Uusi-Rauva et al, 2012;Li et al, 2016b), result in perinuclear clustering of lysosomes. During movement, lysosomes sometimes tubulate in a process that might involve attachment to both kinesins and dynein pulling in opposite directions (Mrakovic et al, 2012;Li et al, 2016b). Lysosome dispersal and tubulation can also be induced by specific stimuli.…”
Section: Lysosome Positioning and Motilitymentioning
confidence: 99%
“…Rab9 interaction with a Golgi-tethering factor, GCC185, promotes interaction with Rab6, Arl1, and the CLASP microtubule-anchoring protein and is suggested to integrate dynein-mediated delivery with docking of endosome-derived vesicles to the Golgi (Hayes et al 2009). Additional insights into the regulation of Rab7 and Rab9 endosome motility-cooperativity with Arflike (Arl) proteins and kinesin-interacting proteins-have in part been gained through analyses of how bacterial pathogens usurp RabGTPase effectors during the establishment of an intracellular niche (Jackson et al 2008;Garg et al 2011;Mrakovic et al 2012;Stein et al 2012b). What emerges from the composite work is that Rab GTPases interact in a nucleotide-dependent manner with microtubule motor complexes and thereby directly control cytoskeletal translocation.…”
Section: Rab Gtpases and Microtubule-dependent Translocationmentioning
confidence: 99%